Development and validation of a situational anxiety scale screening assessment among adults with type 2 diabetes during COVID-19 at a tertiary centre in Chennai, India - Subramani Poongothai; Satish Latha; Mokkapati Lalasa; Karthikeyan Swetha; Viswanathan Mohan (Journal of Diabetology, 2023)
Aim: The aim of this study was to develop and validate the situational anxiety scale (SAS) during COVID-19 among adults with type 2 diabetes attending a tertiary diabetes center in Southern India. Materials and Methods: A total of 100 individuals aged from 18 to 65 years with type 2 diabetes attending a tertiary care diabetes center completed a structured SAS at two visits. The first visit (visit 1) survey was conducted in April 2021 and the second visit (visit 2) survey was conducted in March 2022. The SAS was administered to all 100 individuals. The State Trait Anxiety Inventory Scale (STAI-S) consisting of 20 questions was administered to the same 100 individuals in addition to the SAS during Visit 2. Results: The SAS showed good internal consistency for visit 1 (α = 0.855) and visit 2 (α = 0.795). Exploratory factor analysis showed four factors and explained 69% of variance. The four factors identified were as follows: (1) fear, (2) desire for COVID-free state, (3) lack of interest and energy, and (4) financial worries. A weak positive correlation was observed between SAS visit 2 and STAI-S, and it was statistically significant (r = 0.223; P = 0.026). Conclusion: The SAS is a valid and reliable tool for measuring situational anxiety during pandemics and post-COVID anxiety levels, which can help in the development of a holistic approach.